Investigation of the Frequency of Accessory Ostium in the Maxillary Sinus in Patients Referred to the Radiology Department of the Faculty of Dentistry, Azad University of Isfahan in 2021-2022 - Navid Motamedi; Azadeh Torkzadeh; Hoda Haerian (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2023)
Introduction: Maxillary sinus drains through the primary maxillary ostium into the infundibulum, then flows through the hiatus semilunaris into the middle meatus and communicates with the nasal cavity. The maxillary sinus ostium is located approximately at the most superior part of the medial wall of the sinus. Accessory maxillary ostium (AMO) may play a role in sinusitis, but the effect of heredity or environment on the presence or absence of AMO is unknown.The aim of this study was to assess the primary and accessory maxillary ostium. Methods: In this descriptive-cross-sectional study, 130 Cone Beam Computed Tomography scans (260 sinuses in total) from the maxilla of patients referred to the Department of Oral and Maxillofacial Radiology, School of Dentistry of Isfahan Azad University were examined in Isfahan City, Iran (in the year 2021-2022). Measurements were performed in the coronal section by On Demand 3D software. Statistical analysis was performed by T-Test, Exact fisher, Shapiro-Wilk and Spearman tests through SPSS statistics version 16. Results: The mean diameter of primary maxillary ostium was 1.33 ± 0.45 on the right and 1.33 ± 0.5 on the left, respectively. AMO was observed in 64% of the left sinuses and 38.5% of the right sinuses. Increased sinus mucosal thickness was seen in 26% of the right sinuses and 28% of the left sinuses, and finally Mucous Retention Cyst in 9% of the right sinuses and 8% of left sinuses, respectively. Conclusion: Primary maxillary ostium size was not statistically significant related to the variables of age, sex and the presence of AMO, but on the right side, the average primary maxillary ostium size is less if there is increase in the thickness of the sinus mucosa than when there is no increase in the thickness.